The experience of using calcium carbide for the deoxidation of steel to replace aluminum in the conditions of OJSC «BSW – Management company of the holding «BMC» - О. M. Grudnitsky (Литьë и металлургия, 2020)
The article deals with issues related to the use of calcium carbide in steelmaking, instead of secondary aluminum and other deoxidizing materials, in order to reduce the cost of deoxidizing steel and slag.It was assumed that reducing the content of aluminum in the metal of the reinforcing steel grade would improve its spillability, and by improving the spillability, the yield of usable metal would increase. It was also expected that as a result of the use of calcium carbide for deoxidizing the coating slag in the ladle, the degree of contamination of cord steel with non-metallic inclusions would decrease.During the tests, the optimal amount of additive material was determined. In General, as a result of the work carried out, it was found that calcium carbide can be used for deoxidation of slag and metal during extra-furnace steel processingThe methods of adding the material are described in detail. The results of this work are presented.